The Relationship Between Carotid Artery Intima-Media Thickness and Duration and Glycemic Control in Type 2 Diabetes Mellitus Patients with Peripheral Artery Disease (PAD) - Richard Raja Rampisela; Raden Suhartono; Aria Kekalih (Eduvest - Journal of Universal Studies, 2026)
Type 2 Diabetes Mellitus (DMT2) is associated with several complications, including Peripheral Artery Disease (PAD). Carotid Intima-Media Thickness (CIMT) has been recognized as an early marker of subclinical atherosclerosis, reflecting vascular changes in DMT2 patients. The relationship between disease duration and glycemic control with CIMT in PAD patients is still not fully understood, especially in Indonesia. A cross-sectional study was conducted with 40 DMT2 patients diagnosed with PAD. CIMT was measured using high-resolution Doppler ultrasound. Glycemic control was assessed based on HbA1c levels, with patients categorized based on a threshold of 7%. Data were analyzed using chi-square tests and multivariate logistic regression. A significant relationship was found between DMT2 duration and glycemic control with CIMT thickness (p<0.05). Patients with a disease duration of more than 2 years have a higher chance of experiencing an increase in CIMT. Similarly, poor glycemic control (HbA1c ≥7%) is strongly associated with an increase in CIMT. Long-term DMT2 and poor glycemic control are major contributors to increased CIMT, reflecting a greater burden of atherosclerosis in PAD patients.  Early intervention and optimal glycemic control are essential in preventing cardiovascular complications in this population